2022
DOI: 10.1039/d2qo00422d
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed [4 + 4] cycloadditions for highly diastereo- and enantioselective synthesis of functionalized benzo[b]oxocines

Abstract: Asymmetric cycloaddition reactions represent a powerful strategy for building up complex molecular architectures, especially those with medium-sized rings. Herein, we disclose a highly diastereo- and enantioselective cycloaddition strategy that involves...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Recently, several series of eight-membered oxocine derivatives 13 have been generated through the cascade transformations based on [4 + 4] annulation reactions of conjugated heterodienes with 1,4-dipolar species. 15,17,20,21,23…”
Section: Synthesis Of Oxocine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several series of eight-membered oxocine derivatives 13 have been generated through the cascade transformations based on [4 + 4] annulation reactions of conjugated heterodienes with 1,4-dipolar species. 15,17,20,21,23…”
Section: Synthesis Of Oxocine Derivativesmentioning
confidence: 99%
“…Although o -QMs have been successfully utilized in the asymmetric annulation to synthesize 5–7 membered rings, the enantioselective cycloaddition of o -QMs for the synthesis of eight-membered rings containing adjacent all-carbon quaternary and tertiary stereocenters had not been achieved until the Li and Liu group developed a Pd-catalyzed [4 + 4] annulation for the highly diastereo- and enantioselective generation of functionalized benzo[ b ]oxocines in 2022. 21 In the presence of a catalytic amount of Pd 2 (dba) 3 ·CHCl 3 and a chiral phospharamidite ligand ( L1 ), the decarboxylative asymmetric [4 + 4] cycloaddition between vinyl o -quinone methides (vinyl o -QM) 28 and γ-methylidene-δ-valerolactones (GMDV) 29 afforded the corresponding optically active benzo[ b ]oxocine derivatives 30 in moderate to excellent yields with excellent enantioselectivities and moderate to high diastereoselectivities (Scheme 4). DFT calculations were performed to illustrate the pathway of the asymmetric annulation reaction.…”
Section: Synthesis Of Oxocine Derivativesmentioning
confidence: 99%
“…The same group further extended the scope of dipolarophiles to ortho -quinone methides 158 , leading to the enantioselective synthesis of functionalized benzo[ b ]oxocines bearing adjacent all-carbon quaternary and tertiary stereocenters (Scheme 33). 76 DFT calculations revealed that the conjugate addition step was likely to be the enantio-determining step.…”
Section: Cyclization Involving π-Allyl Palladium Zwitterionsmentioning
confidence: 99%
“…Due to their unique chemical structures, seven- and eight-membered cyclic molecules are beginning to be applied in pharmaceuticals. 1 For instance, (−)-colchicine, 1 a an alkaloid that inhibits cell mitosis, can be used clinically to treat cancer and gout. Similarly, taxol 1 b and cephalotaxine 1 c are also known to inhibit many types of cancer cells.…”
Section: Introductionmentioning
confidence: 99%